2017
DOI: 10.4236/epe.2017.91002
|View full text |Cite
|
Sign up to set email alerts
|

Energy Targeting for a Brewing Process Using Pinch Analysis

Abstract: The rising cost of energy and environmental concerns have led the brewing industry to search for techniques of reducing energy consumption in brewery operations. In this paper, pinch analysis was applied to a typical Ugandan based brewery process to target for the energy requirements of the process. Hint software was used for the analysis. At the chosen ΔTmin of 10˚C, the minimum cooling and heating utility requirements of the brewery studied were determined as being 4862.21 kW and 8294.21 kW respectively, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Pinch technology has demonstrated exceptional success in the works of Adnan et al (2017), Ajao andAkande (2009), andAdejoh et al (2013), in which considerable amounts of energy were recovered, resulting in a cost-effective design. In the works of and Tibasiima and Okullo (2017), better energy recovery was accomplished in the food industry, indicating that wherever heating and cooling occurs, there is a potential opportunity. Several literatures were reviewed on pinch analysis of units in the refinery, Ajao and Akande (2009) worked on "Energy Integration of Crude Distillation Unit using Pinch Analysis."…”
Section: Hamidu U; Ahmed S I; Hamza U Dmentioning
confidence: 99%
“…Pinch technology has demonstrated exceptional success in the works of Adnan et al (2017), Ajao andAkande (2009), andAdejoh et al (2013), in which considerable amounts of energy were recovered, resulting in a cost-effective design. In the works of and Tibasiima and Okullo (2017), better energy recovery was accomplished in the food industry, indicating that wherever heating and cooling occurs, there is a potential opportunity. Several literatures were reviewed on pinch analysis of units in the refinery, Ajao and Akande (2009) worked on "Energy Integration of Crude Distillation Unit using Pinch Analysis."…”
Section: Hamidu U; Ahmed S I; Hamza U Dmentioning
confidence: 99%
“…The process of determining this minimum is referred to as trade-off between energy cost and capital cost in economic analysis of chemical plants. The *Corresponding author: abubakara@abu.edu.ng doi: http://dx.doi.org/10.4314/njtd.v17i3.5 minimum is known as optimum annual total cost and the minimum temperature difference at which this optimum is obtained is known as optimum minimum temperature difference (Attarakih et al, 2013;Rokni, 2016;Tibasiima and Okullo, 2017). Next is the determination of existing annual energy cost ( ) of the FCC unit which was achieved by applying Equation (3) to the existing utility thermal data.…”
Section: ) Determination Of Reduction In the Total Annual Costmentioning
confidence: 99%
“…The technology is based on thermodynamic principles that provides a systematic approach for energy saving with a wide range of applications in many chemical processes (Yoro et al, 2019). Although the application of this technology is most pronounced in oil and gas industries (Marton et al, 2017;Akpa et al, 2018;Ulyev et al, 2018), its use can be found in bioprocessing industry (Anastasovski et al, 2107), sugar production industry (Barambu et al, 2017), brewing industry (Tibasiima and Okullo, 2017) and cement industry (Verma and Kumar, 2017). It has also been used in addressing project selection problem (Pritam et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rising energy‐related costs and environmental concerns have led breweries to search for techniques for the reduction of energy consumption 9 . Breweries have started to consider the concept of sustainability and cleaner production in their processes, rethinking the impact of activities on the environment and seeking strategies to minimize solid waste generation and emissions.…”
Section: Introductionmentioning
confidence: 99%